Affiliating Through Agreements: The Context of Antenatal Consultations. Issue 2 (2nd April 2016) - Petraki, Eleni; Clark, Shannon
Abstract : In the field of antenatal care, there is limited research studying communication between midwives and pregnant women in authentic consultations. This paper addresses this research gap. Based on transcripts of 16 antenatal consultations from a private obstetric practice, we examine agreements as examples of affiliation in the consultations. Using conversation analysis, we discuss ways that agreement is accomplished in this institutional setting. We identify clusters of back-to-back agreements between midwives and women and upgraded and high-grade agreements. Through agreements, midwives validate and endorse women's knowledge while also claiming their own knowledge about issues of pregnancy. Through these conversational strategies, the midwives enact institutionally relevant goals of providing support and treating the woman as having knowledge and expertise about her body and pregnancy, goals which are aligned with clinical practice guidelines for antenatal care and the code of ethics for midwives.